ORGANIC CARBON, NITROGEN AND THE STABILITY OF SOIL AGGREGATES IN AREAS CONVERTED FROM SUGAR CANE TO EUCALYPTUS IN THE STATE OF ALAGOAS - Medeiros,Aldair de Souza (2018)
ABSTRACT The conversion of areas cultivated with sugarcane into eucalyptus forests can promote improvements in the physical, chemical and biological properties of the soil. Within this context, the aim of this study was to evaluate the changes in the stocks and levels of carbon and nitrogen and soil-aggregate stability in an area of transition from sugarcane to eucalyptus in the State of Alagoas, Brazil. The study was carried out on a rural property, located in the district of Atalaia. The systems under evaluation consisted of four areas, one cultivated with sugarcane for approximately 20 years, taken as the reference area for the study, and three adjacent areas cultivated with eucalyptus forest, at 1, 3 and 6 years of age. Bulk density, the levels and stocks of carbon and nitrogen, and the soil aggregation index were all determined. The conversion of a sugarcane plantation under conventional tillage with straw burning into eucalyptus plantations promoted an increase in the levels and stocks of carbon and nitrogen in the soil; it also reduced bulk density and increased the water stability of aggregates. The results show that the conversion of sugarcane into eucalyptus in the Atlantic Forest region of Alagoas may be an alternative for promoting carbon sequestration and improving soil quality.